LOCAL WISDOM AS A MODERATOR OF TECHNOLOGY ADOPTION AND SME PERFORMANCE: EVIDENCE FROM CENTRAL JAVA - Glenda Angeli; Ahmad Shibghatalloh (Universitas PGRI Semarang, 2026)
This study examines whether local wisdom strengthens or weakens the contribution of technology adoption to the performance of small and medium enterprises (SMEs). Digitalisation is widely promoted as the principal lever of SME competitiveness in Indonesia, yet the cultural setting in which adoption actually takes place is seldom modelled explicitly. Data were gathered through a structured questionnaire distributed to SME owners and managers in Central Java and analysed using partial least squares structural equation modelling (PLS-SEM) with SmartPLS. The measurement model satisfied the criteria for convergent validit, internal consistency, and discriminant validity, while the structural model achieved an acceptable fit. Technology adoption exerts a positive and significant effect on SME performance (p = 0.008), and local wisdom exerts a considerably stronger one (p < 0.00). The interaction term is significant but negative ( p < 0.001), indicating that local wisdom substitutes for rather than complements technology adoption. Digitalisation policy therefore needs to be designed around established cultural practice rather than against it.